Becoming a resonant leader : - McKee, Annie (Harvard Business Press, 2008)
Practical and inspiring, Becoming a Resonant Leader is your hands-on guide to developing emotional intelligence, renewing and sustaining yourself and your relationships, and taking your leadership to a whole new level. This book is ideal for anyone seeking personal and professional development and for consultants, coaches, teachers, and faculty to use with their clients or students.